Determinan Uang Kartal Yang Beredar Di Indonesia Sebelum Dan Setelah Penerapan QRIS - Angger Prasetyan Adi; Thomas Andrian; Tiara Nirmala; Nurbetty Herlina S.; Ukhti Ciptawaty (CV. Multi Kreasi Media, 2023)
This study aims to analyze the impact of variables related to electronic money transactions, national income, deposit rates, and the implementation of QRIS as a payment method on the demand for currency in Indonesia from 2015 to 2022. The data used in this study consist of quarterly secondary data from January 2015 to December 2022 in Indonesia. The data processing method employed is the Error Correction Model (ECM) analysis.The findings of this study indicate that the GDP variable has a positive and significant effect on the demand for currency in both the short and long term. The variables related to electronic money transactions also have a positive and significant impact on the demand for currency in both the short and long term. On the other hand, the deposit interest rate variable has a negative and significant long-term effect on the demand for currency. The variable representing the implementation of QRIS shows a negative and insignificant effect on the demand for currency. However, in the long run, the QRIS variable has a positive and insignificant effect on the demand for currency.